Tolerance as the Essential Key for Javanese Society in Preserving the Traditional Cultures - Akhda, Najmu Tsaqib (Universitas Islam Negeri Raden Mas Said Surakarta, 2017)
The close relationship between Java and syncretism invites many questions regarding the historical and cultural backgrounds of these two elements. This paper attempts to find out the form of relationship made by the Javanese society and the practice of syncretism. Some literary reviews are presented in portraying the connection of the Javanese society, especially the practices related to Islam, and the practice of syncretism. It is found out that tolerance is the essential key in accommodating Javanese society and syncretism. Indeed, the era of globalization and modernization is one of the challenges in preserving Javanese traditional cultures.